Role of Plant Growth Regulator and Organic Fertilizer in Growth Stimulation and Quality Enhancement of Muskmelon (Cucumis melo L.) - Praptiningsih Gamawati Adinurani; Sri Rahayu; Ratna Mustika Wardhani; Roy Hendroko Setyobudi; Nguyen Ngoc Huu (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The application of Plant Growth Regulators (PGRs) and certain types of fertilizers can enhance plant growth, production as well as sugar content of muskmelon. Aiming to determine the role of PGRs in stimulating growth and to ascertain the ability of both organic fertilizers and biofertilizers to raise the level of sweetness in muskmelons, this study put a split-plot design into work – the main plots were assigned to fertilizers (P0 = no organic fertilizer, P1 = liquid organic fertilizer, P2 = organic biofertilizer) while sub-plots to PGRs (Z0 = no PGRs (water), Z1 = coconut water, Z2 = GA3). The result concluded that biofertilizer (P2) increased the fruit weight by 11.76 % at an average of 2.66 kg. It also boosted the sugar content by 29.53 %, much higher than organic fertilizer at 15.46 %. As for PGRs, GA3 (Z2) was proven to enhance the sweetness in muskmelon by 23.62 %, higher than coconut water at 16.63 %. The net pattern on the rind of the P2 treatment was smooth, while the ones of P1 were rough. The very fragrant aroma was obtainable by applying biofertilizer (P2) and coconut water as PGRs (Z1).